2005
DOI: 10.1097/01.ccm.0000182796.11329.3b
|View full text |Cite
|
Sign up to set email alerts
|

Infusion of the β-adrenergic blocker esmolol attenuates myocardial dysfunction in septic rats*

Abstract: Esmolol infusion in sepsis improved oxygen utilization of myocardium and preserved myocardial function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
108
2
7

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(133 citation statements)
references
References 42 publications
13
108
2
7
Order By: Relevance
“…However, they failed to provide any supporting data, and one may argue that anti-inflammatory effects would unlikely have occurred this swiftly, i.e., after only four hours of treatment (12)(13)(14)(15).…”
Section: Study Design and Findingsmentioning
confidence: 99%
“…However, they failed to provide any supporting data, and one may argue that anti-inflammatory effects would unlikely have occurred this swiftly, i.e., after only four hours of treatment (12)(13)(14)(15).…”
Section: Study Design and Findingsmentioning
confidence: 99%
“…High levels of circulating catecholamines due to ongoing endogenous and pharmacological adrenergic stimulation may partially explain the discrepancy between maintained cardiac contractility in vivo, that clinicians observe at the bedside, and the profound decrease in cardiac contractility seen under laboratory conditions, for example in ex vivo models of cultured myocardial cells [80] and isolated perfused hearts [81]. Adrenergic downregulation, however, results in a reduced cardiac reserve that is unraveled by a reversible hypo-responsiveness to dobutamine in patients with septic shock [82].…”
Section: Underlying Mechanismsmentioning
confidence: 99%
“…In septic animals, β-blockers reduced heart rate though stroke volume was preserved [81,141]. The longer duration of diastole may perhaps allow better diastolic filling.…”
Section: Beta-blockers In Sepsismentioning
confidence: 99%
See 1 more Smart Citation
“…Excessive adrenergic stimulation is harmful to the heart (3). In animal studies, esmolol, a selective beta-1-adrenergic blocker, improves cardiac contractility, stroke volume (SV) and vascular responsiveness to norepinephrine (4)(5)(6). In patients with septic shock who were initially stabilized, Morelli et al showed that esmolol infusion reduced heart rate, increased SV and reduced norepinephrine requirements (7).…”
mentioning
confidence: 99%